ASPEK YANG BERPENGARUH DALAM PENGGUNAAN SISTEM AKUNTANSI PADA UNIT PELAKSANA TEKNIS PELATIHAN KERJA SE-JAWA TIMUR - Puji Rahayu, Dwi (STIE Mahardhika, 2025)
The success of the performance of an accounting information system can be influenced by several factors, including: user involvement in the development of the information system, user education and training programs, top management support and personal engineering capabilities. This study was conducted to determine the Perception of the Work Environment, Level of Education and Accounting Knowledge on the Use of Accounting Systems in the Technical Implementation Unit of Job Training in East Java. The independent variables in this study are Perception of the Work Environment, Level of Education and Accounting Knowledge. Meanwhile, the bound variable is the Use of Accounting System. The type of research uses a quantitative approach with a comparative causal method using a survey. The sampling technique used was purposive sampling and a sample of 89 employees of the finance department was obtained. The instrument used in the study was a questionnaire. The questions used in the questionnaire are arranged based on the Likert scale. The questionnaire measurement uses a validity test and a reliability test that is tested using SPSS v.21 for windows which shows valid and reliable results. The analysis technique used is multiple linear regression analysis with hypothesis testing using t-statistics to test the influence partially and F-statistics to test the influence together which was tested using SPSS v.21 for windows. The results of this study show that the perception of the work environment, education, and knowledge partially and simultaneously has a significant effect on the Use of Accounting Systems in Job Training UPTs throughout East Java. The determination coefficient test also showed that the use of the Accounting System (Y) could be explained by the perception of the work environment (X1), Education (X2) and Knowledge (X3) by 80.2% and the remaining 19.8% explained by other variables that were not studied in the study.